2009
DOI: 10.1111/j.1749-6632.2008.03650.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pituitary Adenylate Cyclase Activating Polypeptide and Its Fragments on Retinal Degeneration Induced by Neonatal Monosodium Glutamate Treatment

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a member of the growing family of neurotrophic and neuroprotective factors playing important roles during neuronal development and protection against different types of injuries, such as Parkinson's disease, excitotoxicity, and ischemia. As shown with other neuronal tissues, we provide evidence that PACAP is protective in the retina against toxic injury induced by monosodium glutamate (MSG) in vivo. The need for characterization of its fragments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
9
18
0
Order By: Relevance
“…In addition, we showed that the PACAP antagonist PACAP6-38 increased cytochrome-c release, caspase-3, JNK activity and decreased phosphoBad, phospho PKA, Bcl-xL, 14-3-3 protein activity [ 66 , 67 ]. These in vivo observations, similarly to the results of Atlasz et al [ 60 ], indicating that endogenously present PACAP has retinoprotective effects in glutamate-induced excitotoxicity.…”
Section: Excitotoxic Injury In the Retinasupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, we showed that the PACAP antagonist PACAP6-38 increased cytochrome-c release, caspase-3, JNK activity and decreased phosphoBad, phospho PKA, Bcl-xL, 14-3-3 protein activity [ 66 , 67 ]. These in vivo observations, similarly to the results of Atlasz et al [ 60 ], indicating that endogenously present PACAP has retinoprotective effects in glutamate-induced excitotoxicity.…”
Section: Excitotoxic Injury In the Retinasupporting
confidence: 79%
“…Similar protection could be seen by PACAP1-27 treatment [ 60 ]. The application of the two widely used PACAP antagonists (PACAP6-38, PACAP6-27) led to a more pronounced degeneration, indicating that, endogenously present PACAP plays a key role against retinal toxicity [ 60 ]. A similar degree of retinoprotection was found using enriched environment, but combining these two neuroprotective strategies (PACAP and enriched environment) did not result in increased neuroprotection in excitotoxic retinal injury [ 63 ].…”
Section: Excitotoxic Injury In the Retinasupporting
confidence: 57%
See 1 more Smart Citation
“…15,16 We also found that PACAP counteracts the ischemia-induced cytokine changes and promotes antiapoptotic pathways. 17 Altogether, these results provide strong evidence that PACAP has potential therapeutic value in ischemic retinopathy.…”
Section: Methodsmentioning
confidence: 75%
“…Ucn 2 treatments alone had no effect on normal control retinas (data and picture not shown). As we have previously described (2,4,6,7,32), retinal tissue from animals treated with MSG showed severe degeneration compared to normal retinas. The IPL was markedly shrunk and the INL and GCL were intermingled (Fig.…”
Section: Resultsmentioning
confidence: 99%